The occurrence of human papillomavirus types in the formation of neoplastic transformation of the epithelium of the cervix in "lesser abnormalies" - Elena G. Sycheva; Niso M. Nazarova; Olga V. Burmenskaya; Vera N. Prilepskaya; Dmitry Yu. Trofimov (IP Berlin A.V., 2020)
Aim. To assess the frequency of human papillomavirus (HPV) occurrence according to the IARC classification in patients with lesser abnormalie of cervical epithelial lesions and analyze their role in the formation of SIL. Materials and methods. The study included 129 HPV-positive women aged 1845 years (average age 34 to 11 years) with cytological conclusion NILM, ASCUS or LSIL. Patients are divided into 3 groups depending on the results of the cytological smear: 1 group (NILM/HPV) 66 (51.2%), 2 group (ASCUS/HPV) 28 (21.7%), 3 group (LSIL/HPV) 35 (27.1%). During dynamic observation for 24 months. A comprehensive clinical-laboratory examination was carried out, including HPV-typing, cytological examination, extended colposcopy every 6 months, sighting biopsy of the cervix (according to the indications). Results. According to the results of the pathomorphological study, squamous intraepithelial lesions neoplasia (cervical intraepithelial neoplasia CIN+) was verified in 59 (71.9%) of the results of the study: LSIL (CIN I) 53 (64.6%), HSIL (CIN IIIII) 6 (4.6%). The morphological diagnosis of LSIL (CIN I) was established in 1 group (NILM/HPV+) in 20 (55.6%), 2 groups (ASCUS/HPV+) 9 (32%), 3 group (LSIL/HPV) 24 (68.6%); HSIL (CIN IIIII) in group 1 2 (5.6%), in 2 group 3 (10.7%) and in the 3 group 1 (2.9%). Conclusions. In patients with lesser abnormalies of cervical lesions in the formation of CIN+ participated HPV group 1 in 79.1%, groups 2A in 5.5%, groups 2B in 15.4% of cases. The HPV high carcinogenic risk (group 1) was involved in the formation of HSIL (CIN IIIII). The neoplastic transformation of the cervical epithelium of the studied patients was caused by the persistence of HPV 16, 58, 39, 18, 51, 68, 56, 82, 35, 52, 53, 35 types.